How Open is the SBES PC Community? - Pacheco, Fabio; Wiese, Igor; Steinmacher, Igor; Cartaxo, Bruno; Pinto, Gustavo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2019)
The Brazilian Symposium on Software Engineering (SBES) is one of the most important Latin American software engineering coferences. In 2019 it completes its 33rd edition. Over these years, many researchers participated in the SBES attending the conference, submitting papers, or reviewing papers. In particular, the researchers that participated in the program committee, playing the reviewers' role, are fundamentally important to the whole event since their evaluations (e.g., deciding whether a paper is accepted or not) have the potential of drawing what SBES is now. Knowing that diversity is an important aspect of any group work, in this paper we wanted to understand how diverse (in terms of gender and geographic location) is the SBES program committee community. Among the findings, we observed that although the number of participants in the SBES PC increased over the years, most of them are men (~80%) and from the Southeast and Northeast of Brazil, with very few members from the North region.